Carbon nanomaterial‐based copolymer of styrene–divinylbenzene resins: Efficient interaction through graphene/CNTs polymer network. Issue 1 (30th July 2014) - Li, Yanan; Yu, Fengping; He, Wenjun; Yang, Weimin
ABSTRACT Carbon nanotubes (CNTs) and graphene were separately incorporated into the cross‐linked network of styrene–divinylbenzene composites via in situ suspension polymerization. The prepared copolymers were first chloromethylated and then aminated with trimethylamine to obtain ion exchange resins (IERs). The CNTs‐based and graphene‐based composites exhibited good dispersion throughout the polymer matrix with strong interaction within the network. Remarkable enhancement in antiswelling properties and thermal stabilities confirmed that graphene showed better compatibility and stronger interfacial adhesion than CNTs. The structural and thermal properties of the CNTs‐based and graphene‐based IERs were also significantly improved even at low loadings of 0.4 wt % compared with those when no CNTs and graphene were added. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41234.